Six-month stability of individual differences in sports coaches' burnout, self-compassion and social support. (July 2022) - Ackeret, Nadja; Röthlin, Philipp; Allemand, Mathias; Krieger, Tobias; Berger, Thomas; Znoj, Hansjörg; Kenttä, Göran; Birrer, Daniel; Horvath, Stephan
Abstract: Using a three-wave prospective cross-lagged panel design, the study examined six-month stability of burnout, self-compassion and social support among sports coaches in terms of measurement invariance, mean-level change, rank-order stability, and structural stability. The participating coaches ( N = 422; M age = 44.48, SD = 11.03) completed an online questionnaire measuring self-compassion, social support, coach burnout and demographics at baseline and two follow-ups at three months and six months. The various forms of stability were assessed using structural equation modeling. There was no significant mean-level change in burnout, self-compassion, or social support, and all three constructs exhibited measurement invariance. Rank-order stability remained relatively high, ranging from 0.78 to 0.94 across the three time points. For all three constructs, covariances between latent factors were invariant over time, indicating high structural stability. While self-compassion and social support were positively related, both were negatively related to coach burnout. These results confirm the importance of preventing and addressing symptoms of burnout, low self-compassion and poor social support in sports settings. Highlights: Using structural equation modeling, three different types of stability were explored. Self-compassion, social support and burnout symptoms exhibit high stability during six months. Intervention and prevention may be especially important due to high stability scores. Coach burnout is negatively related to self-compassion and social support. Self-compassion and social support are positively related.